Thermal soaring in tropicbirds suggests that diverse seabirds may use this strategy to reduce flight costs - Baptiste Garde (Marine Ecology Progress Series, 2023)
Thermal soaring can offer substantial reductions in flight cost, but it is often assumed to be confined to a relatively narrow group of fliers (those with low wing loading relative to their body mass). Using high-frequency movement data, including magnetometry and GPS, we identified thermal soaring in a seabird previously thought to use only flapping flight: the red-tailed tropicbird Phaethon rubricauda. We tracked 55 individuals breeding on Round Island, Mauritius, and examined the environmental conditions that predicted thermal soaring in 76 trips (ranging from 0.8 to 43 h, mean = 5.9 h). Tropicbirds used thermal soaring and gliding flight for 13% of their flight time on average (range 0-34%), in association with both commuting and prey-searching/pursuits. The use of thermal soaring showed strong variation between trips, but birds were more likely to soar when flying with tailwinds. This enables them to reduce their flight costs without a substantial increase in trip duration, which is pertinent in the breeding season when they are constrained by time and the need to return to a central place. Birds may therefore be able to increase the amount of thermal soaring outside the breeding season. Overall, we suggest that thermal soaring may be more widespread than previously thought, given that birds without specific morphological adaptations for this behaviour can soar for extended periods, and the bio-logging approaches best-placed to detect thermal soaring (high-frequency GPS/magnetometry) tend to be used during the breeding season, when thermal soaring may be less likely.